Estudio multicéntrico saturna 2640 saturación de oxígeno en unidades de recién nacidos a una altura de 2640 metros sobre el nivel del mar (2014)
OBJECTIVE: The goal was to determine reference ranges for pulse oxygen saturation (SpO2) values in the first 15 minutes after birth for at term and preterm infants at a height of 2640 mts above sea level (Bogotá, Colombia) METHODS: Infants were eligible if the mother had a minimum stay in Bogota of three months before birth and that had a normal physical exam at birth and at discharge. Infants were excluded if they received supplemental oxygen or any type of assisted ventilation. SpO2 was measured with a sensor applied to the right hand and right foot as soon as possible after birth; data were collected every 2 seconds. RESULTS: We studied 295 infants. The mean gestational age was 38.5 weeks and birth weight was 3083 gr. For all 295 infants, the 3rd, 10th, 50th, 90th, and 97th percentile values for preductal SpO2 at 1 minute were 8%, 14%, 56%, 78%, 82%, respectively, those at 5 minutes were 43%, 55%, 76%, 88%, 91% and those at 10 minutes were 60%, 72%, 86%, 94%, 96%. The values for posductal SpO2 at 1 minute were 13%, 18%, 48%, 68%, 78%, those at 5 minutes were 32%, 46%, 69%, 84%, 89% and those at 10 minutes were 59%, 69%, 84%, 93%, 95%. We present percentile charts for all groups of infants. CONCLUSION: These data represent reference ranges for SpO2 in the first 15 minutes after birth for preterm and term infants, which are different from those, reported at sea level.